INCIDENCE AND SEVERITY OF COFFEE LEAF RUST, CERCOSPORIOSIS AND COFFEE LEAF MINER IN COFFEE PROGENIES - Lima, Amador Eduardo de; Sampaio Junior, Hudinilson Gilberto; Castro, Elisa de Melo; de Carvalho, Samuel Pereira; da Silva, Fabiano França; Júnior, Sebastião de Lima; de Carvalho, Alex Mendonça (Coffee Science - ISSN 1984-3909, 2018)
Coffee leaf rust is the main disease of this crop, however cercosporiosis and coffee leaf miner can also cause significant damage when they reach high levels of infestation. Plant genetic improvement for resistance is one of the best tools for controlling plant diseases. The objective in this work was to identify F3 progenies of Coffea arabica with resistance to coffee leaf rust, which present a lower incidence and severity of cercosporiosis and coffee leaf miner. The treatments were constituted by 10 progenies, besides two cultivars coffee leaf rust susceptible, used as a control. The experimental design was a randomized block design (RBD), with two replicates, each block consisting of 12 plots randomly distributed, each corresponding to one treatments. The following characteristics were evaluated: coffee leaf rust intensity and severity, cercosporiosis and coffee leaf miner, plants vegetative vigor, grain maturity uniformity and plants height. The progeny averages were grouped by the Scott & Knott test at 5% probability. Progenies 27, 30 and 15 were selected, since they presented low incidence in relation to coffee leaf rust, cercosporiosis and coffee leaf miner, and will be used to continue the breeding program.